Increasing long jump performance through plyometric exercises - Sin, Tjung Hauw; Ruslin, Budi Indra (COUNS-EDU: The International Journal of Counseling and Education, 2019)
Low athlete’s long jump performance is attributed to the unsystematic training approach. Therefore, this study aimed to determine the effect of plyometric training on athlete performance. It was a quasi-experiment comprising of 32 athletes who were selected through purposive sampling. The instrument used in the long jump test is under the standard of the Indonesian Athletics Association (PASI), and the data analysis used a t-test. The results of the data analysis showed significant differences in athlete performance before and after plyometric training. This study recommends adjusting athletes’ long jump performance using Plyometric Exercises.